Comparison of the Effectiveness of Taro Leaf Stalk Extract (Colocasia Esculenta) with Gentamicin Sulfate Cream in the Wound Healing Process in White Rats - Paudilah, Paudilah; Raviah, Nur; Lestari, Dwiana; Lestari, Setiawati; Parliana, Parliana (International Journal Labs, 2023)
The purpose of this study was to determine the comparison of the effectiveness of taro leaf stalk extract (Colocasia esculenta) with gemtamicin sulfate cream in the wound healing process in white rats. This research is a quantitative research with a pure experimental approach. The results of this study consisted of the results of a comparison of the area of early and late wounds in the research rat group, the results of a comparison of the initial wound area and the average wound for 14 days, the results of a pre-post comparison with the research rat group. The results of research on the wound healing process using taro leaf stalk extract stated that the ratio of wound area at the beginning and end between taro petiole extract and control (NaCl) was insignificant, this is because 0.9% Nacl fluid is an effective physiological fluid for wound care by maintaining moisture, keeping granulation dry so that the wound remains in a balanced state that is not dry nor wet.